2020
DOI: 10.1002/micr.30647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vascularized periosteum on revitalization of massive bone isografts: An experimental study in a rabbit model

Abstract: Introduction In the last years, limb salvage has become the gold standard treatment over amputation. Today, 90% of extremity osteogenic sarcomas can be treated with limb salvage surgery. However, these reconstructions are not exempt from complications. Massive allografts have been associated to high risk of nonunion (12–57%), fracture (7–30%) and infection (5–21%). Association of vascularized periosteum flap to a massive bone allograft (MBA) has shown to halve the average time of allograft union in clinical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…These areas were characterized by high osteoblast cellular density along the necrotic trabecula; they were slowly reabsorbed and simultaneously replaced with new viable bone. This process seems to be similar to the “creeping substitution” described in humans [ 37 , 38 ]. These results led us to implant ON-BM-MSCs at 2 weeks after ON induction and collect FHs at 2 weeks after MSC implantation.…”
Section: Resultssupporting
confidence: 73%
“…These areas were characterized by high osteoblast cellular density along the necrotic trabecula; they were slowly reabsorbed and simultaneously replaced with new viable bone. This process seems to be similar to the “creeping substitution” described in humans [ 37 , 38 ]. These results led us to implant ON-BM-MSCs at 2 weeks after ON induction and collect FHs at 2 weeks after MSC implantation.…”
Section: Resultssupporting
confidence: 73%
“…When harvesting a fibula flap, in order to obtain a long enough vessel pedicle, it is usually necessary to strip from the central end of the fibula segment, which might contain a part of the periosteum, forming a vascularized periosteum. It has been reported that vascularized periosteum can accelerate bone graft substitution into a newly formed bone 12 . Second, fracture repair theory maintains that mesenchymal stem cells from the broken end of the osteotomy could become distributed along the vascular pedicle, where they differentiate into osteoprogenitor cells and then into osteoblasts, leading to the new bone formation 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Grafted periosteal stem cells can effectively promote bone healing and improve genetically induced pseudojoint disease and critical size defect in elderly mice [29][30][31]. The implantation of periosteal stem cells provides germplasm resources for the production of biomimetic periosteal substitutes, which can effectively enhance transplantation healing and repair effects [34].…”
Section: Discussionmentioning
confidence: 99%